PENGARUH KEMASAN STARCH-BASED PLASTICS (BIOPLASTIK) TERHADAP MUTU TOMAT DAN PAPRIKA SELAMA PENYIMPANAN DINGIN - Tajul Iflah, Sutrisno dan Titi Candra Sunarti TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
Losses of horticulture product were caused by several reasons, one of them was the un-approriate post-harvest handling. One of the post-harvest method that could maintain the quality of the horticulture product is controlling the storage temperature and packaging techniques to that product. The objectives of this research were to determine the characteristics of horticultural products (tomato and bell pepper) in the cold storage that were packed with bioplastics and high density polyethylene (HDPE). The sample of packed products stored at three temperature levels (5, 10, and 15oC) for 21 days. The results showed that the types of plastic influenced respiration rate (CO2 production rate). The tomatoes packased with bioplastic had climateric phase at the day of 21th which was layer than the one of HDPE. However, bell pepper packsed with bioplastic started senescence phase at 9th day which was taste than the one HDPE at 12th day.Keywords: bioplastic, cold storage, tomato, bell pepper